2005
DOI: 10.1152/ajpgi.00557.2004
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of mechanotransduction by specialized low-threshold mechanoreceptors in the guinea pig rectum

Abstract: The guinea pig rectum, but not the colon, is innervated by a specialized class of distension-sensitive mechanoreceptors that have transduction sites corresponding to rectal intraganglionic laminar endings (rIGLEs). Rectal mechanoreceptors recorded in vitro had low threshold to circumferential stretch, adapted slowly, and could respond within 2 ms to mechanical stimulation by a piezo-electric probe. Antagonists to ionotropic N-methyl-D-aspartate (NMDA; CGS 19755, memantine) and non-NMDA (6,7-dinitroquinoxaline-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
58
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 56 publications
4
58
2
Order By: Relevance
“…Of the four groups, the accelerating stretch-response function of rectal muscular afferents significantly differed from the other three groups, of which none differed from each other. In related studies, the guinea pig rectum was reported to be densely innervated by a distinct population of LT, slowly adapting mechanoreceptors with specialized intraganglionic laminar endings (IGLEs), representing a group of afferent endings not found more proximally in the colon (22,41). Rectal IGLEs, which have not been described in the mouse, terminate in the myenteric plexus between circular and longitudinal muscle layers (22); they would likely have been categorized functionally as rectal muscular afferents in the present study.…”
Section: Discussionmentioning
confidence: 77%
“…Of the four groups, the accelerating stretch-response function of rectal muscular afferents significantly differed from the other three groups, of which none differed from each other. In related studies, the guinea pig rectum was reported to be densely innervated by a distinct population of LT, slowly adapting mechanoreceptors with specialized intraganglionic laminar endings (IGLEs), representing a group of afferent endings not found more proximally in the colon (22,41). Rectal IGLEs, which have not been described in the mouse, terminate in the myenteric plexus between circular and longitudinal muscle layers (22); they would likely have been categorized functionally as rectal muscular afferents in the present study.…”
Section: Discussionmentioning
confidence: 77%
“…In the present study, HF afferents were the most sensitive and rapidly firing class. This profile suggests that their peripheral terminals may be rectal IGLEs (33,34,65). They fire to small amounts of stretch and continue to encode without saturating to distensions into the noxious range (64).…”
Section: Discussionmentioning
confidence: 99%
“…Rectal wall distension is a factor that influences the excitation of mechanoceptors that are involved in monitoring the filling state and the contraction level of the rectum in humans and cats [24,25] . Detection of mechanical deformation by mechanoceptors containing specialized intraganglionic laminal endings, which are found in dense afferent innervations, has been described in the guinea pig rectum [26,27] . Rectal contentinduced stretching of the rectal wall is sufficient to initiate the defecation reflex in humans [28] .…”
Section: Discussionmentioning
confidence: 99%